Bloom - Westcott, Sarah (Liverpool University Press, 2021)
Bloom, Westcott's second collection, approaches the cultural and physical spaces where human and non-human lives co-exist. These poems are attuned to a tender, bleeding world in which 'all flesh is grass' and language is matter. These are poems of resistance: attentive to non-human life, 'eternal and plaintive ... counter-balanced, strange.'